Peran Teknologi Informasi Pada Akuntansi Sektor Publik Dalam Pencegahan Fraud - Nugrah Leksono Putri Handayani (Jurnal Manuhara : Pusat Penelitian Ilmu Manajemen dan Bisnis, 2023)
This study aims to determine the role of information technology in public sector accounting in preventing fraud that occurs in public sector organizations. The research conducted was a literature review research based on articles appropriate to the research topic for further analysis. The result of this research is that there are fraud prevention methods which include technical strategies and preventive strategies. The technical strategy includes efforts to prevent fraud through the use of privacy officer services, IoT access, managing data access, establishing timely reporting, and controlling data in real time. The preventive strategy is in the form of developing a fraud detection system that is run using machine algorithms, data mining, and meta learning methods.